Hispanic Ethnic Density May Be Protective for Older Black/African American and Non-Hispanic White Populations for Some Health Conditions: An Exploration of Support and Neighborhood Mechanisms. Issue 1 (3rd April 2021) - Flores, Melissa; Ruiz, John M; Butler, Emily A; Sbarra, David A
Abstract: Background and Purpose: Hispanic ethnic density (HED) is associated with salubrious health outcomes for Hispanics, yet recent research suggests it may also be protective for other groups. The purpose of this study was to test whether HED was protective for other racial-ethnic groups. We tested whether social support or neighborhood social integration mediated the association between high HED and depressive symptoms (CES-D) and physical morbidity 5 years later. Lastly, we tested whether race-ethnicity moderated both main and indirect effects. Methods: We used Waves 1 (2005–2006), and 2 (2010–2011) from The National Social Life, Health, and Aging Project, a national study of older U.S. adults. Our sample was restricted to Wave 1 adults who returned at Wave 2, did not move from their residence between waves, and self-identified as Hispanic, non-Hispanic White (NHW), or non-Hispanic Black (NHB; n = 1, 635). We geo-coded respondents' addresses to a census-tract and overlaid racial–ethnic population data. Moderated-mediation models using multiple imputation (to handle missingness) and bootstrapping were used to estimate indirect effects for all racial–ethnic categories. Results: Depressive symptoms were lower amongst racial-ethnic minorities in ethnically (Hispanic) dense neighborhoods; this effect was not stronger in Hispanics. HED was not associated with physical morbidity. Sensitivity analyses revealed that HED was protective for cardiovascular events in all racial–ethnic groups, but not arthritis, or respiratory disease. Social support and neighborhood social integration were not mediators for the association between HED and outcomes, nor were indirect effects moderated by race–ethnicity. Conclusions: This study offers some evidence that HED may be protective for some conditions in older adults; however, the phenomena underlying these effects remains a question for future work. Abstract : The density of Hispanic residents in a neighborhood may be protective for 5-year, depressive symptoms, and cardiovascular events for both older adults of Hispanic/Latino(x) ethnicity and other racial-ethnic groups.